Psicoeducação familiar na demência - Gonçalves-Pereira, Manuel (2011)
Introduction: Across the last decades, ageing has largely contributed to position dementia as a huge public health problem, reflecting the burden on service users and their social networks, namely families and informal carers. In health services, family issues regarding dementia frequently lead to referrals. However, at service or community levels, family needs are often underestimated or unmet. In this study, we aimed to describe family interventions in dementia and to review the evidence for the efficacy and effectiveness of family psychoeducation in particular. Methods: The review is based on the relevant literature, but is not intended to be systematic. Results: There are several forms of family intervention in dementia, providing family-carers with psychoeducational strategies or support, or with an alternative emphasis on systemic interventions and classical family therapy. Regardless of their clinical focus, all these interventions may be informed by health promotion principles and values. Family psychoeducation, for instance, aims to develop knowledge and skills making it easier to cope with the strain of dementia caregiving. There is evidence that this may lower family stress, while some psychoeducational interventions may additionaly focus on carers' positive mental health. Conclusions: Several primary, secondary or tertiary prevention strategies regarding dementia would be strengthened by population-based developments in mental health literacy, as related to brain aging and similar topics.